Studens Mathematical Problem Solving Ability in Elementary School: The Effect of Guided Discovery Learning - Amini, Fitri; Munir, Sirajul; Lasari, Yufi Latmini (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
This study aims to determine the effect of the Guided Discovery Learning l Model on the mathematical problem solving abilities of elementary school students. The research is a quasi-experimental research. This research was conducted at 01 Suayan, Akabiluru District. The sample uses Simple Random Sampling. The instrument in this study was a test of students' mathematical problem solving abilities followed by a hypothesis tested using the T-Test. In general, the results showed that the average mathematical problem solving ability of students in the experimental class was higher than the control class and was supported by the results of the hypothesis test for problem solving ability t-count was greater than t-table. Then the research hypothesis is accepted. Thus the Guided Discovery Learning Model has an effect on students' mathematical problem solving abilities in elementary schools.